Pengenalan Konsep Dasar Animasi 2D dan 3D kepada Anak SMA/SMK di Wilayah Provinsi Banten - Suni, Eugenius Kau; Sutresno, Stephen Aprius; Sihombing, Denny Jean Cross; Christanto, Henoch Juli; Bata, Julius Victor Manuel; Airlangga, Gregorius; Setiawan, Yohanes Evan (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2023)
IGiven the rapid development of technology, education in the field of technology becomes crucial for everyone. One of the roles of technology education in fostering someone's creativity can be achieved through learning about things that require creativity, such as animation in the digital world. The Information Systems Program at Atma Jaya Catholic University of Indonesia organized a community service activity in the form of a workshop on November 25, 2023, covering the introduction to the basic concepts of 2D and 3D animation. The workshop was facilitated by Edwar Juanda, S.Ds., M.Ikom, as the speaker, and was attended by 90 participants from high schools and vocational schools in various areas around the Banten province. The workshop proceeded smoothly, and the participants appeared very enthusiastic and active throughout the event. Particularly during the workshop session, participants took turns trying out Virtual Reality tools provided by the speaker. The evaluation through a questionnaire received a positive response from participants with a score of 4.12, indicating agreement. It is hoped that this workshop will provide a broader insight into the younger generation regarding the application of technology, especially in the creation of 2D and 3D animations.